The ART of responsible communication : leading with values every day - Remund, David L. (Giving voice to values on business ethics and corporate social responsibility collection., 2015)
This book is a how-to communications guide for business executives and other leaders like you. The intent is to help you identify and understand some simple yet pivotal ways in which you can take greater responsibility for communication, and substantially improve the vitality and adaptability of your colleagues and your organization. You will learn to define and honor strong values and better streamline your thoughts and actions, in accordance with those values. Above all, you will learn how to consistently and efficiently communicate with all those who have a vested stake in your organization. You will become an expert at responsible communication, and, in turn, relationship-building.